Level of social cohesion of Malaysian youths as a community of practice in a youth development program - Yasmin Yaccob,; Mohamad Ibrani Shahrimin Adam Assim,; Nurul Hidayu Mat Jusoh, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper describes the level of social cohesion of Malaysian youths as a community of practice based on the perspective of social learning theory. Youths’ social environment was examined as the medium of interactions to measure their levels of social cohesion. . Community of practice of youths focused on the major domains of development, and their practice through active participation in a youth development program. The application of the framework of community of practice was measured to ascertain the level of social cohesion among youths in Malaysia. This study employed both quantitative and qualitative approaches. A total of 265 respondents consist of youths who were actively participating in the Duke of Edinburgh International Award. The level of social cohesion among the youths was 63.4%.The findings indicate that the more community program conducted, the higher the level of social cohesion among youth. The parameters of social cohesion were also examined by analyzing youths’ participation and engagement in the award development program. Sustainability of youth development program in Malaysia is found to dependent on levels of youths’social cohesion.